Correlation of prolactin and thyroid disorders in infertile women - Sharma, Priyanka; Pal, Anita; Sood, Rajeev; Jaswal, Saroj; Thakur, Suman; Sharma, Anupam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to review the impact of thyroid status on the fertility and to study the prevalence of hyperprolactinaemia in infertility. Methods: A total of 150 subjects were divided into 3 groups: 50 primary infertility, 50 secondary infertility and 50 controls. The incidence of hyperprolactinaemia and thyroid disorders was studied in all the three groups. Results: The incidence of hyperprolactinaemia was 41% in all infertile subjects (60% with primary and 22% in secondary infertility) and 6% in controls. The incidence of hypothyroidism was 17% in infertility (18% in primary and 16% in secondary infertility) and 8% in controls. Conclusions: In this study there is a positive correlation between increased prolactin levels and hypothyroidism and such patients’ exhibit ovulatory failure. All patients with infertility should undergo prolactin levels and thyroid profile.